Molecular Dynamics Simulations to Investigate the Influences of Amino Acid Mutations on Protein Three-Dimensional Structures of Cytochrome P450 2D6.1, 2, 10, 14A, 51, and 62 - Fukuyoshi, Shuichi; Kometani, Masaharu; Watanabe, Yurie; Hiratsuka, Masahiro; Yamaotsu, Noriyuki; Hirono, Shuichi; Manabe, Noriyoshi; Takahashi, Ohgi; Oda, Akifumi (PLOS ONE, 2016)
Many natural mutants of the drug metabolizing enzyme cytochrome P450 (CYP) 2D6 have been reported. Because the enzymatic activities of many mutants are different from that of the wild type, the genetic polymorphism of CYP2D6 plays an important role in drug metabolism. In this study, the molecular dynamics simulations of the wild type and mutants of CYP2D6, CYP2D6.1, 2, 10, 14A, 51, and 62 were performed, and the predictions of static and dynamic structures within them were conducted. In the mutant CYP2D6.10, 14A, and 61, dynamic properties of the F-G loop, which is one of the components of the active site access channel of CYP2D6, were different from that of the wild type. The F-G loop acted as the “hatch” of the channel, which was closed in those mutants. The structure of CYP2D6.51 was not converged by the simulation, which indicated that the three-dimensional structure of CYP2D6.51 was largely different from that of the wild type. In addition, the intramolecular interaction network of CYP2D6.10, 14A, and 61 was different from that of the wild type, and it is considered that these structural changes are the reason for the decrease or loss of enzymatic activities. On the other hand, the static and dynamic properties of CYP2D6.2, whose activity was normal, were not considerably different from those of the wild type.